2018
DOI: 10.21608/ijhth.2018.31516
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the 4Ps on Passengers' Purchasing Decision-Making: the Case of LCCs

Abstract: The liberalization of air transport industry in the USA by 1978 and then in the early 1990s in the Eu, that was resulted in having the LCCs, has led to significant changes in the global air transport sector .The success of LCCs, and their acquisition of a large market share in the air transport sector are due to the fact that such firms rely mostly on providing the air transport services with a competitive price for passengers. The study pursues to highlight on the experience of LCCs, and the extent of their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…These companies are Air Cairo, Air Arabia, Flynas, Nile Air, Air Italy, and Agean Air. These airlines depend mainly on Cairo International Airport and Borg El Arab Airport for several reasons as follows (Abdelhady et al, 2018):…”
Section: Egypt Field Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These companies are Air Cairo, Air Arabia, Flynas, Nile Air, Air Italy, and Agean Air. These airlines depend mainly on Cairo International Airport and Borg El Arab Airport for several reasons as follows (Abdelhady et al, 2018):…”
Section: Egypt Field Results and Discussionmentioning
confidence: 99%
“…Hence, the deregulation of the aviation sector has certainly had the great influence of growing the number of LCCs, which have become a dominant competitor in the air transport market. Furthermore, liberalizing the air aviation sector is advantageous so as to attract more competitors to this industry, which leads to lower airfares (Abdelhady et al, 2018).The figure 7 presents the effect of liberalization on market access to EU by LCCs.…”
mentioning
confidence: 99%
“…Due to the characteristics of these services' marketing, it is concluded that the factors of people, process, and customer service are significant and determine the decision to use service products. (Abdelhady et al, 2019) so that this study adds these variables to represent the marketing mix besides place and price. This study took 5 (five) marketing mixes to determine their purchasing decisions for College services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Customer service is the core of service products (Abdelhady et al, 2019). How can universities provide quality, serve students in the learning process and get benefits from the process?…”
Section: Customer Servicementioning
confidence: 99%
“…They concluded place was the most influential variable in attracting viewers to offline film screenings [17]. The results of Abdelhady et al study in 2019 using random sampling and multiple regression analysis showed a significant positive relationship between place, promotion, and product of marketing mix and passenger purchase decision [18].…”
Section: Placementioning
confidence: 99%